Are glycoprotein inhibitors safe during percutaneous coronary intervention in patients on chronic warfarin treatment? - Lahtela, Heli; Karjalainen, Pasi P.; Niemelä, Matti; Vikman, Saila; Kervinen, Kari; Ylitalo, Antti; Puurunen, Marja; Porela, Pekka; Nyman, Kai; Hinkka-Yli-Salomäki, Susanna; Airaksinen, K. E. Juhani (Thrombosis and Haemostasis, 2009)
The aim of this study was to evaluate the safety of glycoprotein IIb/IIIa inhibitors (GPIs) during percutaneous coronary intervention (PCI) in patients on chronic warfarin therapy due to atrial fibrillation (AF).We analysed all consecutive AF patients (N = 377, mean age 70 years, male 71%) on warfarin therapy referred for PCI in seven centres. Major bleeding, access site complications and major adverse cardiovascular events were recorded during hospitalisation. A total of 111 patients (29%) received periprocedural GPIs with a wide inter-hospital variation in their use (range 3–68%).The use of GPIs increased with the severity of the disease presentation and 49% of patients with ST-elevation myocardial infarction received GPIs. Mean periprocedural international normalised ratio (INR) of patients who received GPIs was 1.89 (range 1.1–3.3). Major bleeding was more common in the patients treated with GPIs (9.0% vs. 1.5%, p = 0.001) than in those without GPIs, but there was no difference in major adverse cardiovascular events between the groups. In multivariable analysis, use of GPIs (odds ratio [OR]???????????5.1, 95% confidence interval [CI]???????????1.3–20.6, p = 0.02) and old age (OR 1.2, 95% CI 1.0–1.3, p = 0.02) remained as the only independent predictors of major bleeding. Also after adjusting for propensity score, GPIs remained as a significant predictor of major bleeding (OR 3.8, 95% CI 1.03–14.1, p = 0.045). In the GPI group, major bleeding was not predicted by INR level or warfarin pause. GPIs increase the risk of major bleeding events irrespective of periprocedural INR levels and should be used with caution in this fragile patient group.
Keywords: Antithrombotic treatment; angioplasty; anticoagulation; bleeding complications